“... protect me, Lord, from contempt, protect me from hatred, God”. When Words Express Contempt - Gałczyńska, Alicja (Respectus Philologicus, 2023)
The article is devoted to the concept of contempt, understood as a feeling of disrespect and aversion and a sense of superiority towards someone towards whom our contempt is directed. It is an emotion of a social nature, winding up a spiral of hatred. Contempt presupposes the speaker’s superiority, who considers himself superior to the person/group of people he is speaking to. I treat the rhetoric of contempt as an element of verbal aggression, which is sometimes expressed through various linguistic means. Here I would like to show how words change their meaning and start to express contempt and hatred towards another human being. Referring to the determinants of hate speech indicated by Michał Głowiński (ruthlessness of reason, objectification of the „hero” of the statement, dichotomy of values, conspiracy view of reality, arbitrariness of assessments and depersonalized sender), I indicate why the use of the term LGBT ideology is such an immoral way of using language. Language analyses focus on statements from public discourse – they were taken primarily from Internet portals and social media.
Keywords: the rhetoric of contempt; hate rhetoric; public discourse; ideology; LGBT